PROBLEMS IN RESOLVING PRESS CASES THROUGH THE INDONESIAN NATIONAL POLICE - Andhiya Moza Faris; Aldira Dean Pratama; Dede Kania (Warmadewa Press, 2024)
This research is motivated by the phenomenon of the polemic faced by the press against the Police, which is related to the lack of certainty in resolving cases in the press even though there is an MoU made between the Press Council and the Police. This research aims to find a problem that has existed between the Police and the Press Council such as the MoU (Police and Press Council) which then questioned its significance such as its legal strength in resolving press cases. Then provide the best advice in resolving press cases by the police of the Republic of Indonesia. The research method used is normative juridical, with a statute approach. The results obtained from this research show that the MoU between the Press Council and the Police has the same legal force as agreements in general. Then the settlement of cases in the Police can be resolved one of them using the restorative justice method by using police discretion as an effort to keep press people from feeling criminalized and maintaining the image of the police.